'A High Tory and an American upon my own Principles': James Boswell, the American Revolution, and Royalist Constitutionalism, 1775–1783. Issue 1 (2nd January 2023) - Brown, Zachary
ABSTRACT: In the early 1770s, American revolutionaries argued that the British Empire was a federation of autonomous states united by the person and prerogatives of the King. This royalist vision of empire, often called 'dominion theory, ' has been the subject of considerable scholarly work but little has been done to examine how metropolitan advocates for royal power – British Tories – responded to these colonial arguments. Focusing on the Scottish biographer and royalist James Boswell, this article argues that the theoretical possibility of Tory-American convergence played an underappreciated role in the imperial debates of the 1770s-80s. Whig supporters of the North ministry denounced dominion theory and similarly conceived peace proposals as threatening to revive Tory tyranny, while anti-American Tories claimed that colonial royalism was insincere and ineffective. Pro-American Tories like Boswell, however, not only embraced American arguments for an empowered crown but also had their vision of royalist empire adopted by the doomed Carlisle Peace Commission of 1778. The ultimate failure of conciliation on the terms of dominion theory, and the subsequent debates over East India Company reform, solidified a different model of empire where parliamentary sovereignty and prerogative remained compatible.